E-Administration as an Approach to Improving the Academic Performance of Law Faculty Members: An Experience at the University of Misan - Reyath Thea Azeez Alsafo; Mohammed Ahmed Waham; Mohammed Raoof Al-Musawi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The study sought to find the effect of E-administration in its various aspects on functional performance in the University of Misan/ College of Law. The target population was all members of the College of Law, N=40. The questionnaire was used as a tool for data collection, and distributed to the research groups, of which 33) questionnaires were collected and statistically analyzed. Data Processing and Analysis The SPSS 26 software was used to process and analyze the questionnaire information to calculate the arithmetic mean, standard deviation, correlation coefficient, and impact coefficient. One of the very significant findings was that